2013
DOI: 10.1016/j.sdentj.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of four methods for stain removal from direct resin-based composite restorative materials

Abstract: Compositions of resin-based composite resins play an important role in their susceptibility to stain and their amenability to stain removal procedures. Home bleaching showed good results for the three materials, while office bleach was the least effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 25 publications
5
26
0
12
Order By: Relevance
“…The L* coordinate change was generally a higher value and a lighter shade. Regarding stain removal, these results appeared to contradict Al-Nadedh et al 19 that using a light in the bleaching process increases the effect of bleaching on the composite, and they suggested that light-activated bleaching had a greater whitening effect on stained composites and might be more beneficial in bleaching restorative resins than in bleaching tooth structures. Using CP-based bleaching agents for resin composite stain removal will raise some esthetic concerns, including possible color mismatches between the restored resin composite and the surrounding tooth structure.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The L* coordinate change was generally a higher value and a lighter shade. Regarding stain removal, these results appeared to contradict Al-Nadedh et al 19 that using a light in the bleaching process increases the effect of bleaching on the composite, and they suggested that light-activated bleaching had a greater whitening effect on stained composites and might be more beneficial in bleaching restorative resins than in bleaching tooth structures. Using CP-based bleaching agents for resin composite stain removal will raise some esthetic concerns, including possible color mismatches between the restored resin composite and the surrounding tooth structure.…”
Section: Discussionmentioning
confidence: 77%
“…These results are consistent with previous studies that evaluated the effects of carbamide peroxidebased bleaching agents on resin composites stain removal. Al-Nadedh et al 19 reported that bleaching with 10% CP for four hours daily for 2 weeks was superior to both polishing and 38% hydrogen peroxide-based in-office bleaching procedures for stain removal and can effectively remove stains from all tested materials and return them to a clinically acceptable color. Villalta et al 20 studied the effect of different concentrations of CP (16,18 and 35%) on stain removal from resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os tratamentos estéticos, destacam-se as restaurações de resina composta e o clareamento dental, por este se tratar de um procedimento conservador e seguro 2,4 . Já a resina composta, apesar de ser tão procurada, apresenta algumas desvantagens, sendo uma das quais o fato de que, quando exposta a certas substâncias e influências no meio oral, estas fazem com que sofra mudança de cor 5,6 e, consequentemente, ocorre a perda do padrão estético que se desejava.…”
Section: Introductionunclassified
“…Algumas manchas extrínsecas podem ser parcial ou totalmente removidas por meio de escovação dentária com uso de dentifrício, profilaxia realizada pelo cirurgião-dentista ou ainda repolimento das restaurações 12,13 , para evitar a substituição desnecessária. Entretanto, quando alguns destes casos não são bem sucedidos, o clareamento dental é uma abordagem conservadora bastante indicada e utilizada na atualidade 5,14 .…”
Section: Introductionunclassified
See 1 more Smart Citation